Analisis Yuridis Akibat Hukum Pada Sengketa Tumpang Tindih Sertifikat Tanah Pada Putusan Nomor 58/Pdt/2022/Pt.Plk - Jovita Sesylia; Evi Evi; Elin Sudiarti; Heriamariaty Heriamariaty (Jurnal Ilmiah Global Education, 2026)
The problem of overlapping land certificates reflects the weakness of the land administration system in Indonesia and the lack of thoroughness of the National Land Agency (BPN) in verifying physical and legal data. This study aims to analyze the legal consequences of overlapping land certificate disputes as stipulated in the Palangka Raya High Court Decision Number 58/PDT/2022/PT.PLK, and to examine the procedures for canceling duplicate certificates in accordance with applicable laws and regulations, specifically the Regulation of the Minister of ATR/BPN Number 11 of 2016 and Number 21 of 2020. The methodology used is normative juridical, utilizing a statutory approach and case studies. The results of the study indicate that certificates issued earlier have higher legal force based on the Prior Tempore Potior Jure principle, while certificates issued later and proven to be administratively flawed must be canceled. The National Land Agency (BPN) can be held legally responsible if it is negligent in the certificate issuance process. This research also found problems with the norms in the Basic Agrarian Law, Government Regulation No. 24 of 1997, and Regulation of the Minister of ATR/BPN No. 11/2016 which caused a lack of synchronization between the authority of the BPN and the courts. Therefore, legislative reform and digitization of land data are very important to build a land administration system that is orderly, accountable, and guarantees legal certainty for the community.